Družbeno nesprejemljivi diskurz na Facebookovih straneh novičarskih portalov - Vehovar, Vasja (Teorija in praksa, 2020)
The paper examines the comments sections of the most visited Facebook news pages in Slovenia between 2010 and 2017. The research focuses on socially unacceptable discourse (SUD) concerning two topics then dividing the public; namely, the refugee crisis and the rights of LGBT people. The results show that the share of comments with SUD is high and stable, representing approximately half of all the comments on both topics and all three news pages. Surprisingly, there are few differences among the news outlets as regards the internal structure and characteristics of SUD, although significant differences were found in the extent of SUD among the portals. On the other hand, the results did not confirm the presence of organised hate cam-paigns or the connectedness of commentators. The results offer one of the first insights into the characteristics of the commenting culture in Slovenia, the timeframe of commenting and the connectedness of commentators.
Keywords: analiza diskurza; analiza omrežij; begunci; Commentary; Discourse; Diskurz; družbena sprejemljivost; Facebook; Komentar; komentarji; LGBT; novičarski portali; odnos do drugačnih; Portali; Portals